The Importance of Persuasion Strategies in Doctors’ Social Media Messages - ASSEGAFF, Syafiq B.; LILIWERI, Alo; SERAN, Alexander (PT Keberlanjutan Strategis Indonesia, 2023)
This study investigates how doctors employ persuasion strategies (Ethos, logos, and pathos) on Instagram to influence the health behaviors of their followers during the COVID-19 pandemic. Analyzing three influential doctors on social media (DSMIs), the research applies Aristotle's persuasive strategies to understand how these doctors craft messages that drive behavior change and enhance COVID-19 awareness among their 581 followers. Employing a mixed methods approach within the pragmatism paradigm, the study utilizes interviews, literature reviews, content analysis, and surveys for comprehensive data collection. The study reveals that approximately 41% of followers demonstrated a firm intention, with an additional 43% showing a solid intention to change their attitudes and behaviors. About 84% expressed a strong commitment to adopting a healthier lifestyle. The research also identified followers who initially had doubts or confusion about COVID-19 due to misinformation. However, it became convinced of its existence after following the DSMIs' posts, mainly through engaging video content. Engagement is more significant for video content than photos, with pathos, Ethos, and logos effectively fostering engagement. Around 52,438 (314,000) DSMI followers shifted from initial skepticism to meaningful positive attitude transformations, driven by successful engagement through pathos, Ethos, and logos. The study underscores the significance of delivering persuasive and appealing messages to influence behaviors positively. It suggests active social media participation can extend beyond the pandemic, fostering ongoing health awareness.